Application of The Single Index Model to Determine Optimal Portfolio Composition in IDXG30 Stocks (2021-2024) - Ariantara, Made Arvin; Oktayanti, Ni Putu Riza; Astawa, I Made; Rahim, Laode (Journal of Economics and Management Scienties, 2025)
This study investigates optimal portfolio construction using the Single Index Model (SIM) with a focus on IDXG30 stocks in Indonesia, an index known for its high liquidity and market capitalization. In the context of growing investor interest in efficient yet practical portfolio strategies, this research aims to determine the composition of an optimal portfolio, allocate fund proportions accordingly, and assess the expected return and risk associated with the resulting investment. The study adopts a descriptive methodology with a quantitative approach. Secondary data were collected from 30 IDXG30-listed companies during the 2021–2024 period, including monthly stock prices, Jakarta Composite Index (JCI) values, and Bank Indonesia’s 7-Day Reverse Repo Rate (BI7DRR) as the risk-free rate. The analysis follows the SIM framework, utilizing Excess Return to Beta (ERB) as the key selection metric. Results show that 15 companies qualified for the optimal portfolio, with the top five weighted stocks being NISP (53.96%), MIDI (7.57%), AUTO (7.53%), BBCA (6.61%), and MAPA (4.86%). The expected return of the constructed portfolio is 1.99%, with an estimated risk of 0.0765%. These findings demonstrate that the SIM can effectively guide investors in identifying high-performing stocks and achieving favorable risk-return trade-offs, particularly in emerging markets. The study provides relevant insights for fund managers and policymakers in designing index-based investment instruments.